ANALYSIS OF GENETIC DIVERSITY IN GRAPE ( YSIS OF GENETIC DIVERSITY IN GRAPE (Vitis vinifera itis vinifera L.) CULTIVARS BY ISSR (Inter Y ISSR (Inter-Simple Sequence Repeats) Mark Simple Sequence Repeats) Markers - P.R. CHALKE,; , P.V.PATIL,; N.R. MARKAD, (The Bioscan, 2019)
The genomic DNA isolated from 19 grape cultivars (Vitis vinifera L.) were subjected to PCR amplification using 34 ISSR primers. Of 34 primers, 22 showed polymorphism and produced 182 bands, of which 149 were polymorphic with an average of 81.86 % polymorphism, each primer thus produced on an average 6.77 polymorphic bands. The size of amplified product was ranging from 171.31 bp to 2154.67 bp. The number of amplicons generated by each primer varied from 3 bands (ISSR 828) to 16 bands (ISSR 890). The similarity coefficient between the genotypes varied from 0.51 to 0.96 indicating low to moderate diversity among the genotypes. The UPGMA based cluster analysis using dice similarity coefficient grouped nineteen grape cultivars into two major clusters. The cluster A had 13 cultivars, while in cluster B there were 6 cultivars. The dendogram generated based on UPGMA method of cluster analysis using ISSR marker data revealed little different but similar grouping of genotypes into two major clusters viz., cluster A and cluster B. The distribution of the cultivars in the dendogram was mostly consistent with the known pedigree information and the morphological attributes. Overall results indicate that ISSR markers appears to be reliable and efficient for the assessment of genetic relationship among grape cultivars.